Analisis Finansial Agribisnis Jagung Pada Zona Agroekologi IIIay di Timor Barat - Yuniati Fabiola; I Nyoman Sirma; Ernantje Hendrik (Buletin Ilmiah Impas, 2018)
This research has been conducted in the Oenesu Village, Tesabela Village, Bolok Village of West Kupang Sub District and Oesusu Village, Takari Sub District of Kupang District of East Nusa Tenggara Province. The research starting in May-June 2016, with the aim to determine: (1) profitable of corn farming, and (2) financially feasible of corn farming. The method used in this research is survey method. Location research done intentionally (purposive sampling). Types of data collected are primary data obtained from interviews with respondents based on the questionnaire, while secondary data obtained from the institution concerned. To find the first goal, the data were analyzed using analysis of farming. The second purpose were analyzed by financial analysis tools through the calculation criteria NPV, Net- B/C, and Gross B/C. The results showed that: (1) the corn farming in research region are profitable, and (2) the investment on corn farming there are feasible to continued, because the financial analysed conducted with a positively NPV, is Rp 4.653.799,07, the value of Net B/C of 1, and Gross B/C of 1,23 or more than 1.